If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3b+3=-5b+2
We simplify the equation to the form, which is simple to understand
-3b+3=-5b+2
We move all terms containing b to the left and all other terms to the right.
-3b+5b=+2-3
We simplify left and right side of the equation.
+2b=-1
We divide both sides of the equation by 2 to get b.
b=-0.5
| -7.5x+73.8=10.8 | | (21+3y)-3y=14 | | 2x^2+4x+4=40 | | 6(3.5+0.5y)-3y=14 | | 12n-8=13n+18 | | -5+2(x+5)=-5 | | 2x^2+4x+4=36 | | 3.1x-3.9=8.5 | | 34=3(4x+1)-5 | | 6(y-5)=6 | | 6(3.5+0.5)-3y=14 | | 7x^2-48= | | 7n=4n-33 | | -12w+39=7-16w | | 6d+2d-d+9-4d=0 | | 5(x+3)-4(x+2)-3x=7+9x+1 | | 2.6(3.9-5.9)= | | 90=18+8x | | n=8n+28 | | 5x+16=58-2x | | x=2.5+-0.5(1) | | x=2.5+0.5(1) | | 3y+4+y=13+y | | 6y-11(0.5-0.5y)=7+10y | | 4x-3+x=6x-4 | | -5t=-33-15t | | 4=9p-3-8p | | H(t)=4.9t+120t | | 2(x+y)=1+y | | 2(x-4)+3=(2x+5) | | 95+d=100 | | 2(x-7)+3x=2x-8 |